Curing of Maleimidyl Phenol-Formaldehyde Resins Via Esterification and Free Radical Polymerization (Baghdad Science Journal, 2007)
Three phenol-formaldehyde resins having pendant maleimides were prepared by poly condensation of N-(hydroxyphenyl) maleimides with formaldehyde under conditions similar to those in Novolac preparation. The prepared resins were modified by two methods, the first one includes esterification of phenolic hydroxyl groups in the prepared resins via their treatment with benzoyl, acryloyl, methacryloyl and cinnamoyl chlorides respectively in the presence of triethylamine, while the second modification includes free radical polymerization of vinylic bonds in the prepared resins to produce cross-linked thermally stable polymers.